Characterization of culturable bacteria isolated from mesophotic reef sites in Cuba - Ortiz-Guilarte, Eudalys (2021)
The bacterial communities of mesophotic reef sites constitute genetic information of interest due to the particular conditions of temperature, pressure, salinity and availability of organic matter and nutrients in the environment in which they develop. The present work aimed to evaluate the bacterial diversity in waters surrounding the mesophotic reefs of Cuba during the period May-June 2017; as well as some of its biotechnological potentialities. Bacterial cultures were isolated on marine agar medium for two water column depth levels at 10 sampling sites.  Subsequently, the metabolic capacities of the isolates were evaluated and related to the assimilation of different carbon sources and the production of bioactive metabolites.  The results allowed the characterization of 30 bacterial cultures from subsurface-level and 32 from deep-sea waters.  The highest percentage corresponds to Gram positive (G+) sporulated bacilli and Gram negative (G-) bacilli.  Likewise, it was shown that 85.5% of the isolates degrade carbohydrates of different nature and 96.8% produce hydrolytic enzymes with caseinase, gelatinase, lipase or amylase activity.  The ability to degrade petroleum oil and phenolic compounds indistinctly was detected in 61.3% of the isolates.  Among the potentialities of biomedical and industrial interest, surfactant and L-asparaginase activity was detected in 53% and 32% of the cultures, respectively.  For its part, the taxonomic characterization of 40 cultures selected for their metabolic potentials showed that the genus Bacillus presented greater biological activity.  These results constitute the first approach to the characterization of bacterial diversity in mesophotic reef sites of Cuba.